CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN DENGAN KUALITAS LABA SEBAGAI VARIABEL MEDIASI (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2014-2017) - Izzatun Ni’mah; Rr. Tjahjaning Poerwati (Dinamika Akuntansi Keuangan dan Perbankan, 2019)
This study aims to examine and analyze the influence of corporate governance factors on firm value and earnings quality as mediating variables. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange during the 2014-2017 period. The sample in this study was taken by using Purposive Sampling techniques, so as to obtain a sample of 425. The analysis technique used was to use multiple regression and path analysis (path analysis).The results of this study indicate that managerial ownership, institutional ownership and independent commissioners have a positive but not significant effect on earnings quality. Managerial ownership has a positive and significant effect on firm value. Institutional ownership, independent commissioners and earnings quality have a negative but not significant effect on firm value. The quality of earnings has not been able to mediate the influence of managerial ownership, institutional ownership and independent commissioners on the value of the company. Keywords: managerial ownership, institutional ownership, independentcommissioner, profit quality and company value.